2022
DOI: 10.3390/mi14010003
|View full text |Cite
|
Sign up to set email alerts
|

Microextrusion Printing of Multilayer Hierarchically Organized Planar Nanostructures Based on NiO, (CeO2)0.8(Sm2O3)0.2 and La0.6Sr0.4Co0.2Fe0.8O3−δ

Abstract: In this paper, NiO, La0.6Sr0.4Co0.2Fe0.8O3-δ (LSCF) and (CeO2)0.8(Sm2O3)0.2 (SDC) nanopowders with different microstructures were obtained using hydrothermal and glycol–citrate methods. The microstructural features of the powders were examined using scanning electron microscopy (SEM). The obtained oxide powders were used to form functional inks for the sequential microextrusion printing of NiO-SDC, SDC and LSCF-SDC coatings with resulting three-layer structures of (NiO-SDC)/SDC/(LSCF-SDC) composition. The crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…Previous research by various authors has shown the high efficiency of using printing technology to create miniaturized components and devices for alternative energy, electronics, and gas sensing. In particular, it has been demonstrated that approaches such as ink-jet printing [36][37][38][39], aerosol printing microplotter [40][41][42][43] and microextrusion [44][45][46][47][48][49] printing, and pen plottier printing [50][51][52] allow the use of inks of varied viscosity, forming coatings of different thickness and geometry with high accuracy and ensuring high reproducibility of microstructures and functional characteristics of the resulting planar structures.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research by various authors has shown the high efficiency of using printing technology to create miniaturized components and devices for alternative energy, electronics, and gas sensing. In particular, it has been demonstrated that approaches such as ink-jet printing [36][37][38][39], aerosol printing microplotter [40][41][42][43] and microextrusion [44][45][46][47][48][49] printing, and pen plottier printing [50][51][52] allow the use of inks of varied viscosity, forming coatings of different thickness and geometry with high accuracy and ensuring high reproducibility of microstructures and functional characteristics of the resulting planar structures.…”
Section: Introductionmentioning
confidence: 99%
“…The method of inkjet printing using ceramic printing compositions is cost-effective, easily scalable, and allows precise control of the shape, size, and morphology of the printed object [20,22]. Microextrusion or robocasting has also been used for the 3D printing of a SOFC anode based on the NiO/YSZ ceramic composite [23][24][25]. In general, microextrusion has the same advantages as inkjet printing.…”
Section: Introductionmentioning
confidence: 99%